Differential regulation of adipose tissue and vascular inflammatory gene expression by chronic systemic inhibition of NOS in lean and obese rats. Issue 2 (7th February 2014) - Padilla, Jaume; Jenkins, Nathan T.; Thorne, Pamela K.; Lansford, Kasey A.; Fleming, Nicholas J.; Bayless, David S.; Sheldon, Ryan D.; Rector, R. Scott; Laughlin, M. Harold
Abstract We tested the hypothesis that a decrease in bioavailability of nitric oxide (NO) would result in increased adipose tissue (AT) inflammation. In particular, we utilized the obese Otsuka Long Evans Tokushima Fatty rat model (n = 20) and lean Long Evans Tokushima Otsuka counterparts (n = 20) to determine the extent to which chronic inhibition of NO synthase (NOS) with Nω‐nitro‐l‐arginine methyl ester (L‐NAME) treatment (for 4 weeks) upregulates expression of inflammatory genes and markers of immune cell infiltration in retroperitoneal white AT, subscapular brown AT, periaortic AT as well as in its contiguous aorta free of perivascular AT. As expected, relative to lean rats (% body fat = 13.5 ± 0.7), obese rats (% body fat = 27.2 ± 0.8) were hyperlipidemic (total cholesterol 77.0 ± 2.1 vs. 101.0 ± 3.3 mg/dL), hyperleptinemic (5.3 ± 0.9 vs. 191.9 ± 59.9 pg/mL), and insulin‐resistant (higher HOMA IR index [3.9 ± 0.8 vs. 25.2 ± 4.1]). Obese rats also exhibited increased expression of proinflammatory genes in perivascular, visceral, and brown ATs. L‐NAME treatment produced a small but statistically significant decrease in percent body fat (24.6 ± 0.9 vs. 27.2 ± 0.8%) and HOMA IR index (16.9 ± 2.3 vs. 25.2 ± 4.1) in obese rats. Further, contrary to our hypothesis, we found that expression of inflammatory genes in all AT depots examined were generally unaltered with L‐NAME treatment in both lean and obese rats. This was in contrast with the observation that L‐NAME produced a significant upregulation of inflammatory and proatherogenic genes in the aorta. Collectively, these findings suggest that chronic NOS inhibition alters transcriptional regulation of proinflammatory genes to a greater extent in the aortic wall compared to its adjacent perivascular AT, or visceral white and subscapular brown AT depots.